Estudo da aplicação do Problem Based Learning (PBL) no ensino superior de contabilidade - Silva, Carmen Eliana da (2015)
The constant change in the accounting area alongside with the technological evolution have brought about an improvement necessity for methods and techniques, which shall be helpful with the process of inserting students on the job market and also enabling them to have a wider view of the business world by developing the capacity to apply it on their professional lives. In this Scenario the Problem Based Learning PBL method was studied and applied on classes for the subjects Prática contábil informatizada I and II within the Accounting Course of the private college Estácio Europan in Cotia, São Paulo. The PBL was applied for students enrolled in the 4th semester in 2014 and in the 5th semester in 2015.The objective is to test whether this method is well received by students in class, considering that it is student based, differently from the traditional ones. This case was elaborated based on the real needs of a small company, considering a questionnaire developed with Sebrae s information about the reasons for a company to go out of business and the 7 sins of smalls companiesby José Carlos Marion; therefore the students have applied the method considering the identified problems. Further to that they answered a survey regarding the acquired knowledge and the applied method. The results obtained were compared by the means of a Chi-Square (where equal proportions were expected), which allowed to be identified that most of the students have considered the strategy as positive and motivating regarding their learning process and also that they were able to achieve the aimed objective, which means, the acquisition of knowledge upon the subject taught and the theory through the practice experienced by the method. The aforementioned results identify the acceptance of the applied method